Befores & Afters Magazine - Failes, Ian, ....- (S.l. : s.n., 2023)
Issue #8 of befores & afters magazine covers VFX art departments, and features: - MPC on Nope - Wētā FX on Doctor Strange in the Multiverse of Madness - Framestore on Ready Player One and Fantastic Beasts - Digital Domain on Ms. Marvel - Cinesite on The Witcher - Rodeo FX and Pixomondo on HALO - Jellyfish Pictures on Prehistoric Planet - Animal Logic on its USD shorts - Narwhal Studios on The Book of Boba Fett
Keywords: Animation; Visual effects